Implementación de la filosofía Lean Six Sigma en la minería para optimizar la fortificación mecanizada en las excavaciones horizontales 2023 - Ccatamayo Barrios, Johnny Henrry (2025)
The research applied the Lean Six Sigma methodology, DMAIC cycle, to optimize mechanized support on the 745 Bypass in the face of geomechanical instability, reported as a critical problem by the customer. The objective was to design and validate a comprehensive strategy to reduce variability and increase efficiency in structural stability, using indicators such as monthly frequency of rockfalls, percentage of surface area affected by unstable wedges, and overall safety factors (OSF). Initial assessments showed a mean convergence depth of 2.76 cm, although Ppk = 0.37 and Cpk = 0.34 indicated an inability to maintain specifications (base value >1.33). Massif conditions in Zone 4 were characterized by structural systems (N23°E/74°NW) and an RMR range of 48–64, corresponding to domains of fair to acceptable quality. Analyses indicated induced stresses of 9 to 18 MPa in section S1 and safety factors close to 1.2, revealing high operational risk. In terms of intact rock physical properties, porosity ranged from 0.319% to 0.640% and dry density from 2.779 to 4.850 g/cm³, confirming the heterogeneity of the massif. Improvement activities were prioritized based on cause-and-effect analysis: FLAC3D modeling and macro and micro simulations identified critical actions to control instability, collapse risk, and oversizing in support (technical gap, shotcrete thickness, and validated installation methods). The discussion concluded that the application of the Lean Six Sigma approach, validated by numerical and physical modeling, allowed for increased operational safety and efficiency, with high safety factors after the intervention and a proven reduction in variability.